All-Optical Mult~hop Free-Space Optical Communication Systems - Kazemlou, Shabnam (My University, 2010)
Free-Space Optical (FSO) communication systems have recently attracted considerable attention in last-mile applications. High bandwidth, unlicensed spectrum, ease of installation, and high security have made them a good candidate for high data rate transmissions. However, distance-dependent atmospheric turbulence and channel loss degrade the optical link reliability and confine FSO systems to short-haul applications. This thesis addresses innovative all-optical relaying techniques to mitigate the degrading effects of atmospheric turbulence-induced fading by relaying data from the source to the destination using intermediate terminals. The proposed techniques, optical amplify-and-forward (OAF) relaying and optical regenerate-and-forward (ORF) relaying, are deployed in multihop FSO systems to extend the maximum accessible communicating distance of high data rate wireless optical systems.
In all-optical relaying techniques, photo detection is performed once at the receiver and intermediate terminals process optical field envelopes instead of optical intensities. This major difference requires a new definition of channel model for propagation of optical waves through the atmosphere. By using the developed channel model, bit error rate (BER) performance of multihop OAF FSO systems is analyzed through Monte-Carlo simulations. The simulation results indicate that OAF relaying technique mitigates the channel impairments and enhances the BER performance. By employing more relays, longer distances become accessible, however distance improvement decreases due to accumulating background noise at relays. In order to remove background noise effects, another optical relaying technique is developed. The ORF relaying technique eliminates the received background noise at each relay and significantly outperforms OAF systems. For example at high bit rate BR= 10 Gbps, using two equally-spaced OAF relays during a 3 km turbulence-free link increases the total communicating distance by about 1.11 km. Replacing OAF relays by ORF relays extends the total communicating distance to 4.48 km which is 1.66 km longer than the similar OAF FSO system. By deploying more ORF relays, even longer distances are achievable.
Keywords: Electrical and Computer Engineering; Electrical and Computer Engineering